Bank Profitability, Globalisation and Barriers to Entrepreneurship. A Panel Data Analysis for Europe and the United States (1999-2007) - Miltiades N. Georgiou; Nicholas Kyriazis (Kredit und Kapital, 2012)
Bank Profitability, Globalisation and Barriers to Entrepreneurship. A Panel Data Analysis for Europe and the United States (1999-2007) The crux of the present article is that if corporations (as bank clients) are profitable in a globalised economic environment and there are no barriers to entrepreneurship, banks (as lenders to these corporations) are expected to be profitable too. Thus, our proposed model is a link between globalisation, barriers to corporate entrepreneurship and bank profitability. In the present paper it is empirically shown that a reduction in barriers to corporate entrepreneurship definitely has a positive impact on banking profitability, but globalisation (measured by the "trade to GDP" index) can have either a positive impact on banking profitability under certain assumptions concerning the estimation method, or no impact at all under certain assumptions concerning the estimation method. Finally, it is shown that the other two globalisation indices - geographical concentration (trade of goods) as well as FDI - do not matter as far as banking profitability is concerned. In short, the empirical evidence shows that barriers to corporate entrepreneurship seem to be the most crucial factor for banking profitability, while globalisation measured by three different indices does not always play an important role regarding banking profitability determination. The sample covers many European countries, as well as the United States. The econometric model estimation using panel data is made feasible through the Eviews software package. It should be noted that although the present model launches an interesting discussion on the links between globalisation, barriers to entrepreneurship and bank profitability, it cannot provide conclusive evidence, since either globalisation indices are not perfect or (and) estimated regression coefficients depend on the method of estimation. However, the present paper triggers further research on this topic. (JEL L26, G3, O4, C23, G21) – – Die Rentabilität von Banken, Globalisierung und Beschränkungen des Unternehmertums - Eine Analyse von Paneldaten für Europa und die Vereinigten Staaten (1999-2007) Die Crux dieses Artikels liegt darin, dass, wenn Unternehmen (als Bankkunden) in einem globalisierten Wirtschaftsumfeld rentabel sind und es keine Beschränkungen des Unternehmertums gibt, man davon ausgehen darf, dass Banken (als Kreditgeber dieser Unternehmen) ebenfalls rentabel sind. Somit stellt das von uns vorgeschlagene Modell ein Bindeglied zwischen Globalisierung, Beschränkungen des Unternehmertums und Rentabilität von Banken dar. Dieser Artikel enthält den empirischen Beweis, dass eine Absenkung des Niveaus von Beschränkungen des Unternehmertums definitiv eine positive Wirkung auf die Rentabilität von Banken ausübt, jedoch auch, dass die Globalisierung (gemessen als Anteil des Handels am Bruttoinlandsprodukt ("trade to GDP-Index")) unter gewissen Annahmen hinsichtlich der Schätzmethode entweder eine positive Wirkung auf die Rentabilität von Banken haben oder sich gar nicht auswirken kann. Schließlich wird gezeigt, dass zwei weitere Globalisierungsindizes - geografische Konzentration (Warenhandel) und ausländische Direktinvestitionen (FDI) - von keinerlei Bedeutung für die Rentabilität von Banken sind. Kurz gesagt: die empirischen Beweise zeigen, dass Beschränkungen des Unternehmertums für die Rentabilität von Banken der ausschlaggebende Faktor für ihre Rentabilität zu sein scheinen, wohingegen die auf der Grundlage von drei unterschiedlichen Indizes gemessene Globalisierung nicht immer eine wichtige Rolle für die Bestimmung der Rentabilität von Banken spielt. Die Stichprobe umfasst eine Reihe europäischer Staaten sowie die Vereinigten Staaten von Amerika. Die Schätzung eines ökonometrischen Modells auf der Grundlage von Paneldaten wird durch das Eviews-Softwarepaket ermöglicht. Es sollte zur Kenntnis genommen werden, dass, obgleich dieses Modell den Anlass für eine interessante Diskussion über die Bindeglieder zwischen Globalisierung, Beschränkungen des Unternehmertums und die Rentabilität von Banken gibt, es keine schlüssigen Beweise liefern kann, da beide Globalisierungsindizes nicht perfekt sind oder (und) geschätzte Regressionskoeffizienten von der Schätzmethode abhängen. Aber dieser Beitrag stellt einen Anlass für weitere Forschungsarbeiten zu diesem Thema dar. (JEL L26, G3, O4, C23, G21)
Keywords: L26; G3; O4; C23; G21; 330